2009
DOI: 10.1007/s00404-009-1298-3
|View full text |Cite
|
Sign up to set email alerts
|

Residual and recurrent disease rates following LEEP treatment in high-grade cervical intraepithelial lesions

Abstract: LEEP is a basic procedure in the conization performed on patients with CIN II/III. In spite of high recurrence and residual disease rates, this kind of patients requires close monitoring. Follow-up with HPV and PAP-smear tests after LEEP treatment is of great importance in the detection of residual or recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 15 publications
6
42
0
1
Order By: Relevance
“…However, many recurrences and persistence of high-risk HPV DNA were still found (Aerssens et al, 2008). Therefore, a follow-up including HPV detection and Pap-smears of all patients after LEEP is strongly recommended (Baloglu et al, 2010). In contrast, in the MVA E2-treated group, only 5 (3.5%) out of 141 female patients with high-grade lesions showed the appearance of lesions in a period of 2 years after treatment.…”
Section: Discussionmentioning
confidence: 94%
“…However, many recurrences and persistence of high-risk HPV DNA were still found (Aerssens et al, 2008). Therefore, a follow-up including HPV detection and Pap-smears of all patients after LEEP is strongly recommended (Baloglu et al, 2010). In contrast, in the MVA E2-treated group, only 5 (3.5%) out of 141 female patients with high-grade lesions showed the appearance of lesions in a period of 2 years after treatment.…”
Section: Discussionmentioning
confidence: 94%
“…For young women, diagnosis and establishment of the correct degree of the precursor lesion is essential for adopting the appropriate therapeutic intervention to prevent the cervical carcinoma from developing further. LEEP is a conservative treatment, and is indicated in women of reproductive age to avoid complications in the case of a future pregnancy [1,15]. Some investigators have reported that LEEP has no important adverse effects on fertility [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…If these lesions are diagnosed early and treated appropriately, SCC development is interrupted [1,2]. Loop electrosurgical excision procedure (LEEP) is an excellent treatment option for precancerous cervical lesions [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…most of the studies demonstrate that the margins affections increase the risk of illness residual [24,25] significantly. In the study of Houfflin-Debargue et al [26] the patients with positive margins were 36%, in the study of Serati et al [27], 32% of the patients presented margins affections and it was found that this was the factor more important predictor of recurrent illness, the same as in the works of Prato [28] and Baloglu et al [29].…”
Section: Design Methodologicalmentioning
confidence: 68%